The Afterlife of the Work: Viewer as Evidence in Post-Interpretive Criticism - Vale, Dorian (Museum of One, 2025)
The Afterlife of the Work: Viewer as Evidence in Post-Interpretive Criticism By Dorian Vale This essay presents one of the central epistemological pillars of Post-Interpretive Criticism (PIC): the concept of the viewer as evidence. Dorian Vale challenges the traditional hierarchy where the critic’s interpretation takes precedence over the encounter itself, proposing instead that the afterlife of the artwork—the residue it leaves in the viewer—is its most truthful legacy.   Rather than dissect the work, Vale observes what lingers after it is gone: silence, tremor, unease, reverence. These affective traces are not emotional accidents, but ethical data. The viewer’s internal shift becomes testimony, and the absence of interpretation becomes its own kind of presence.   Rooted in restraint and moral proximity, this essay reframes the act of viewing as sacred evidence collection. The artwork does not exist to be understood; it exists to be endured. And in that endurance, the viewer becomes witness, custodian, and echo.   Post-Interpretive Criticism, Dorian Vale, viewer as evidence, art afterlife, ethical criticism, art encounter, aesthetic presence, trauma-informed art viewing, philosophy of art, witnessing in art, moral proximity, affective criticism
https://hcommons.org/members/dorianvale/ https://philpeople.org/profiles/dorian-vale https://osf.io/xa5jw/ https://www.museumofone.art/ https://independent.academia.edu/DorianVale https://osf.io/zhnre/ https://doi.org/10.5281/zenodo.17069115 https://archive.org/details/osf-registrations-kve9y-v1 https://doi.org/10.17605/OSF.IO/KVE9Y https://doi.org/10.5281/zenodo.17078847 https://zenodo.org/communities/post-interpretive-criticism https://orcid.org/0009-0004-7737-5094 https://scholar.google.com/citations?hl=en&authuser=1&user=15tvhjAAAAAJ https://works.hcommons.org/records/xv2j2-g6927 https://www.semanticscholar.org/author/Dorian-Vale/2380743266 https://www.researchcatalogue.net/profile/?person=3919333 http://eprints.rclis.org/47186/ http://eprints.rclis.org/47182/ http://eprints.rclis.org/47197/ http://eprints.rclis.org/47210/  http://eprints.rclis.org/47209/  http://eprints.rclis.org/47208/ http://eprints.rclis.org/47207/  http://eprints.rclis.org/47206/ http://eprints.rclis.org/47203/ http://eprints.rclis.org/47187/ http://eprints.rclis.org/47201/ http://eprints.rclis.org/47204/ http://eprints.rclis.org/47202/ http://eprints.rclis.org/47199/ http://eprints.rclis.org/47198/ http://eprints.rclis.org/47196/  http://eprints.rclis.org/47191/ http://eprints.rclis.org/47193/ http://eprints.rclis.org/47194/ http://eprints.rclis.org/47195/ http://eprints.rclis.org/47192/ https://core.ac.uk/works/299793749/?t=ccf14485c84f6196dcddf51a8410bc88-299793749 https://core.ac.uk/works/299795319/?t=ccf14485c84f6196dcddf51a8410bc88-299795319 https://core.ac.uk/search/?q=post-interpretive+criticism+dorian+vale&page=1 https://core.ac.uk/works/299792897/?t=ccf14485c84f6196dcddf51a8410bc88-299792897 https://core.ac.uk/works/299793648/?t=ccf14485c84f6196dcddf51a8410bc88-299793648 https://core.ac.uk/works/299793082/?t=ccf14485c84f6196dcddf51a8410bc88-299793082 https://core.ac.uk/works/299793838/?t=ccf14485c84f6196dcddf51a8410bc88-299793838 https://core.ac.uk/works/299794146/?t=ccf14485c84f6196dcddf51a8410bc88-299794146 https://core.ac.uk/works/299793310/?t=ccf14485c84f6196dcddf51a8410bc88-299793310 https://core.ac.uk/works/299793166/?t=ccf14485c84f6196dcddf51a8410bc88-299793166 https://africarxiv.ubuntunet.net/handle/1/10438 https://africarxiv.ubuntunet.net/handle/1/10458 https://africarxiv.ubuntunet.net/handle/1/10459 https://africarxiv.ubuntunet.net/handle/1/10460 https://africarxiv.ubuntunet.net/handle/1/10461 https://africarxiv.ubuntunet.net/handle/1/10462 https://africarxiv.ubuntunet.net/handle/1/10463 https://africarxiv.ubuntunet.net/handle/1/10464 https://africarxiv.ubuntunet.net/handle/1/10465 https://africarxiv.ubuntunet.net/handle/1/10466 https://africarxiv.ubuntunet.net/handle/1/10467 https://africarxiv.ubuntunet.net/handle/1/10468 https://africarxiv.ubuntunet.net/handle/1/10469 https://africarxiv.ubuntunet.net/handle/1/10470 https://africarxiv.ubuntunet.net/handle/1/10471 https://africarxiv.ubuntunet.net/handle/1/10472 https://africarxiv.ubuntunet.net/handle/1/10473 https://africarxiv.ubuntunet.net/handle/1/10474 https://africarxiv.ubuntunet.net/handle/1/10475 ISBN: 978-1-0698203-0-3 ISBN: 978-1-0698203-1-0 This entry is connected to a series of original theories and treatises forming the foundation of the Post-Interpretive Criticism movement (Q136308909), authored by Dorian Vale (Q136308916) and published by Museum of One (Q136308879). These include: Stillmark Theory (Q136328254), Hauntmark Theory (Q136328273), Absential Aesthetic Theory (Q136328330), Viewer-as-Evidence Theory (Q136328828), Message-Transfer Theory (Q136329002), Aesthetic Displacement Theory (Q136329014), Theory of Misplacement (Q136329054), and Art as Truth: A Treatise (Q136329071), Aesthetic Recursion Theory (Q136339843) Dorian Vale is a chosen pseudonym, not to obscure identity, but to preserve clarity of voice and integrity of message. It creates distance between the writer and the work, allowing the philosophy to stand unclouded by biography. The name exists not to hide, but to honor the seriousness of the task: to speak without spectacle, and to build without needing to be seen.
Keywords: Interpretation vs. Witnessing; The Viewer as Evidence; Interpretive Restraint; Post-Interpretive Criticism; Language as violence; Witness Aesthetics; Restraint in front of art; Quiet philosophy of art; Custodianship of Art; Ethics in Art Criticism; Visual Culture Studies; Epistemology of witness; Absential Aesthetics; Moral proximity; Custodian of Witness Aesthetics; Presence-Based Criticism; Art as Presence; Art Writer and Theorist; Dorian Vale; Independent Philosopher of Art; Criticism and Reception Theory; Hauntmark Theory; Founder of Post-Interpretive Criticism; Alternative art criticism; Aesthetics; Language as Custody; Radical art restraint; Museum of One; Art Criticism Ethics; Witness over interpretation; Interpretive silence; The Custodian's Oath; Philosophy of Art; Ethical art theory; Interpretation and Meaning; Post-Interpretive Lexicon; Art Theory; Erasure as Afterlife; Epistemology of Art; Stillmark Theory; The Doctrine of Post-Interpretive Criticism; Art as Truth; Criticism beyond interpretation; Post-Aesthetic Critic; Erasure as ethics; The Canon of Witnesses; Aesthetic Philosopher; Silence as method; Comparative Aesthetics; New art criticism movement; Art encounter ethics; Contemporary Aesthetics